SIMULASI MONITORING KEAMANAN MULTI GENERATOR MENGGUNAKAN KURVA KAPABILITAS GENERATOR PEMBELAJARAN NEURAL NETWORK - Zainal Abidin (Universitas Nusa Cendana, 2012)
Generator capability curve at generating developed to monitoring of generator operational safety. Study of generator capability curve is developed with using neural network by Constructive Backprogation (CBP) method. Angle  of generator capability curve used as study input and complex power curve as target of study. Study of best curve got with its nearby generator capability curve with generator capability curve result of study. Result of study of generator capability curve used monitoring Pgen and Qgen result from power flow 150 kV system East Java regional. Security and safety monitoring of generator visualizinged in generator capability curve as result of NN study. Generator capability curve as result of study of NN study have abality of monitoring of change power generator, and solvent of monitoring rest of generator capability and can give information of power (PQ) and generator operating point with ability boundary and generator stability.